3-D exact solution of two-layer plate bonded by a viscoelastic interlayer with memory effect. (15th March 2017) - Wu, Peng; Zhou, Ding; Liu, Weiqing; Lu, Weidong; Fang, Hai
Abstract: An exact solution for simply supported two-layer plate sandwiching a thin viscoelastic interlayer under transverse load is proposed. The deformation of each plate layer is described by the exact three-dimensional linear elasticity equations. The viscoelastic characteristic of interlayer is simulated by the standard linear solid model, considering the memory effect of the material. The shear and transverse normal strains in the interlayer are simultaneously considered in the analysis. The analytical approach is presented to obtain the solution of stresses and displacements in the plate. The present solution can be used as a benchmark to access other simplified solutions for the problem aforementioned. The comparison analysis shows that the finite element solution has a close agreement with the present solution. However, the solution based on Kirchhoff-Love hypothesis is greatly different from the present solution for thick plates. It is indicated that the effect of the transverse normal strain in the interlayer increases with the increase of the interlayer thickness, especially for thick plates. Finally, the influences of geometric and material parameters on the plate deflections are investigated in detail.